3-degree polynomial is f(x )=
![[x^(3 )-(9)/(7) x^(2)+9x-(81)/(7) ]](https://img.qammunity.org/2020/formulas/mathematics/college/rb6dp3kjrvappp8c7hre01kqiietkg0qua.png)
Explanation:
Given that polynomial f(x) is 3-degree polynomial and Zeros/Roots at x=
and x= -3i
In order to find the equation of a 3-degree polynomial, we need 3 roots.
Here, One of Root is real number x=
and another root is an imaginary number x=(-3i)
It is necessary to note that imaginary roots always come in pair of conjugates
Therefore, Comjugate0 of x =(-3i) is 3rd root
Conjugate of (-3i) is 3i
Evaluting equation of polynomial,
=
![[x-3i][x+3i][x-(9)/(7) ]](https://img.qammunity.org/2020/formulas/mathematics/college/ke5ywyegd9qpe2v7rr6xdfcaf16xh1xw4m.png)
=
![[x^(2)-(3i)^(2)][x-(9)/(7) ]](https://img.qammunity.org/2020/formulas/mathematics/college/nb8gqvazsesee1rwrsfcvp08rhfh7r8855.png)
=
![[x^(2)-(9)(i)^(2)][x-(9)/(7) ]](https://img.qammunity.org/2020/formulas/mathematics/college/k9bnnxekal13r2nv8cvp0ujlg4adwwo6c4.png)
=
![[x^(2)+9][x-(9)/(7) ]](https://img.qammunity.org/2020/formulas/mathematics/college/imwf6wpsz9qnp7vcamnvguywozigc32ka6.png)
f(x )=
![[x^(3 )-(9)/(7) x^(2)+9x-(81)/(7) ]](https://img.qammunity.org/2020/formulas/mathematics/college/rb6dp3kjrvappp8c7hre01kqiietkg0qua.png)